Design of Accounting Information System Based on VBA Excel at Islamic Boarding School X Based on Non-Profit Organization Standards - Muhamad Noval A; IGKA Ulupui; Etty Gurendrawati (Indonesian Journal of Business Analytics, 2025)
As a non-profit institution, Islamic boarding schools have an important role in education and character building of the community, but still face major challenges in financial management, especially in terms of transparency, accountability, and recording financial reports according to standards. This study aims to design and implement an Accounting Information System (AIS) based on VBA Excel that is adjusted to the ISAK 335 standard at Islamic Boarding School X. This study uses the Waterfall system development method which includes the stages of needs analysis, system design, implementation, verification, and maintenance.Data collection was conducted through observation, interviews, and literature studies on the financial management of Islamic boarding schools. The results of the study indicate that VBA Excel-based AIS can improve efficiency, accuracy, and speed in the process of recording and reporting finances. This system also facilitates the preparation of financial reports such as financial position reports, activity reports, and cash flow reports in accordance with non-profit organization standards. With the implementation of this system, Islamic boarding schools are expected to be able to improve accountability and transparency in fund management, so as to strengthen stakeholder trust and support the sustainability of the institution.